Christian Love by Søren Kierkegaard on the Basis of His Works of Love. - Jędraszewski, Marek (Filozofia Chrześcijańska, 2014)
This paper is trying to show that Kierkegaard is not a person who only fears and trembles in front of God but who’s attitudes towards God can be described with terms of love first of all. The author is analyzing different notions of love, which are described by Kierkegaard.